Multiple revisions of inflatable penile prosthesis: a case report - Chauvanasmith, Arnantkorn; Buranapitaksanti, Dechapol; Pala, Tippawan (Insight Urology, 2022)
This article presents considerations regarding dilemmas and treatment concerning the revision of inflatable penile prosthesis (IPP) after non-infectious mechanical malfunction. The aim of this report is to improve surgical planning to avoid the most common complications after revision of inflatable penile prosthesis. With greater understanding, implanters could more accurately select patients and provide increased information and advice maximizing the results.